Discourse in traumatic brain injury - Hema N; Shyamala Chengappa (Journal of All India Institute of Speech and Hearing, 2010)
Analysis of discourse production can be chosen as a means for testing cognitive-linguistic abilities of individuals with traumatic brain injury (TBI). The aim of the present study was to assess the cognitive-linguistic abilities in terms of discourse analysis in participants with traumatic brain injury and to compare them with discourse of neurologically intact individuals. The participants included 20 individuals with TBI (closed head injury) and 20 healthy talkers. The task involved use of a conversational topic, “family”. Conversation was audio recorded using computer software and speech sample was transcribed verbatim using IPA and analyzed for discourse parameters using a discourse analysis scale. The results of this study showed a significant difference between the participants with TBI and healthy talkers. Participants with TBI were deficient on certain parameters of discourse. The details are discussed.